Jungnok Park, How Buddhism Acquired a Soul on the Way to China - Dy, Ari (Religions of South Asia, 2013)
Jungnok Park, How Buddhism Acquired a Soul on the Way to China. Sheffield: Equinox, 2012. x + 246 pp. £60. ISBN 978-1-84553-996-2 (hardback). £19.99. ISBN 978-1-84553-997-9 (paperback).